The Role of the School Psychologist Nowadays - Osmanaga, Fatbardha (European Journal of Multidisciplinary Studies, 2022)
The school psychologist fills multiple roles. Changes have been made in the field of public perceptions about the roles of a school psychologist. The main purpose of the paper is to get information about the perception of the students of master’s degree in psychology at the University of Shkoder regarding the school psychologist’s profession. The paper is quantitative research and it it is based on the survey research, descriptive and correlational research. The questionnaire consists of several parts. The first part contains demographic data, such as gender, age, study course, and study program. The second part contains data related to the opinion of students regarding the school psychologist’s profession and the third part contains information about the general perception and students‘perception about the roles of a school psychologist, such as information, identification, assessment, participation in various commissions and intervention. There are given the conclusions and recommendations. The students’ opinion and general perception about the school psychologist profession is good, but it is necessary to improve the perception of students in the following aspects: a) Improving the general perception of students regarding the profession of school psychologist, especially at older ages, at the students of second year Master and at the students of the Master of Sciences study program in Organizational Psychology; b) improving students’ perception of the role of information that the psychologist performs in school; c) improving the perception of second year students about the role of identification and the role of assessment; d) improving the perception of first year students about the role of participation in various commissions and the intervention role. It is also recommended to conduct other studies, to identify the factors that affect students’ perception of the profession of school psychologist, and it is recommended the curricula and the syllabuses review of these study programs.